Elasticity of the Transition State Leading to an Unexpected Mechanical Stabilization of Titin Immunoglobulin Domains - Yuan Guohua (Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim, 2020)
10.1002/anie.201700411